Key Role of Nitrate in Phase Transitions of Urban Particles: Implications of Important Reactive Surfaces for Secondary Aerosol Formation. Issue 2 (24th January 2018) - Sun, Jiaxing; Liu, Lei; Xu, Liang; Wang, Yuanyuan; Wu, Zhijun; Hu, Min; Shi, Zongbo; Li, Yongjie; Zhang, Xiaoye; Chen, Jianmin; Li, Weijun
Abstract: Ammonium sulfate (AS) and ammonium nitrate (AN) are key components of urban fine particles. Both field and model studies showed that heterogeneous reactions of SO2, NO2, and NH3 on wet aerosols accelerated the haze formation in northern China. However, little is known on phase transitions of AS‐AN containing haze particles. Here hygroscopic properties of laboratory‐generated AS‐AN particles and individual particles collected during haze events in an urban site were investigated using an individual particle hygroscopicity system. AS‐AN particles showed a two‐stage deliquescence at mutual deliquescence relative humidity (MDRH) and full deliquescence relative humidity (DRH) and three physical states: solid before MDRH, solid‐aqueous between MDRH and DRH, and aqueous after DRH. During hydration, urban haze particles displayed a solid core and aqueous shell at RH = 60–80% and aqueous phase at RH > 80%. Most particles were in aqueous phase at RH > 50% during dehydration. Our results show that AS content in individual particles determines their DRH and AN content determines their MDRH. AN content increase can reduce MDRH, which indicates occurrence of aqueous shell at lower RH. The humidity‐dependent phase transitions of nitrate‐abundant urban particles are important to provide reactive surfaces of secondary aerosol formation in the polluted air. Plain Language Summary: Recently, aerosol water has received more attention because heterogeneous reactions of SO2, NO2, and NH3 on wet particles accelerate the severe haze formation in north China. Ammonium sulfate and ammonium nitrate (AS‐AN) are key components of fine urban particles. Especially, nitrate concentration keeps increasing in polluted air in China. Our study indicates that the increase of AN content promotes the occurrence of aqueous shell at lower RH. Here we find that most of urban particles generally keep solid core and aqueous shell at RH = 60–80% and aqueous phase at RH > 80%. These findings can clearly explain the role of nitrate in phase transitions and make up the discussion about heterogeneous reactions on particle surfaces during the severe hazes in north China. Humidity‐dependent phase states of particles are useful for interpreting the secondary aerosols' formation in severe hazes as well as in modeling studies. Key Points: Laboratory‐generated ammonium sulfate‐ammonium nitrate (AS‐AN) particles undergo two stage deliquescence and one stage efflorescence Aqueous shell and solid core occur on urban haze particles with relative humidity at 60–80% AN content mainly determines the MDRH of urban haze particles, and AS mainly determines DRH